Rheological Analysis of Zirconia-Hydroxyapatite with Bi-Modal System of Binders; Low-Density Polyethylene and Palm Stearin - Amin, Muhammad Mohamed; Zainal Adelin, Nur Syamimi; Sulong, Abu Bakar; Muhamad, Norhamidi (International Journal of Integrated Engineering, 2023)
The two component micro-powder injection molding (2C-?PIM) process has evolved from ?PIM process because of the increasing demand for multi-functional micro-components applications. In this research work, the selected materials to fabricate micro-sized bi-material parts are zirconia (ZrO2) and hydroxyapatite (HA). ZrO2 is chosen for structural integrity and bio-inert, while HA is mainly chosen for bio-active properties. The reason of employing the multi-component binders is to ensure the flowability of the feedstock. Feedstock rheological characteristics needs to be carefully investigated to avoid any undesirable and inhomogeneous mixture between powder and binder. A common binder system which is comprised of palm stearin and low-density polyethylene (LDPE) were mixed with individual ZrO2 and HA powder particles to prepare for ZrO2 and HA feedstocks. Typically, the feedstocks were obtained ZrO2 and HA powders independently with a binder ratio of 60 wt.% of palm stearin and 40wt.% low-density polyethylene (LDPE). The mixing was carried out in Brabender mixer. Before mixing, critical powder volume percentage (CPVP) analysis was carried out to determine the optimal powder loadings required to prepare the ZrO2 and HA feedstocks. In this research work, the obtained CPVP of ZrO2 and HA powders were 47.0 and 59.0 vol.%, respectively. Based on CPVP analysis, six feedstocks with optimal powder loadings of 43, 44 and 45 vol.% for ZrO2 and 54, 55 and 56 vol.% for HA were prepared. The rheological analysis involving viscosity, shear rate, flow behavior index, activation energy and moldability index was investigated using capillary rheometer. Based on the obtained rheology result, it shows that the overall shear rate and viscosity are within the 2C-?PIM process recommended range. All tested composition shows pseudoplastic behavior. The results of the study found that ZrO2 and HA with optimal powder loadings of 55 vol.% and 44 vol.% have good rheological properties compared to feedstocks with other powder loadings. This is because both materials meet the criteria of good rheological properties which are low viscosity, high shear rate, flow behavior index less than one, low activation energy and high moldability index.